HEAVY METALS IN THE FOOD CHAIN - CONSEQUENCES OF POLLUTING WATER BODIES - Ramchandra, T V; Narayan, N R (Green Chemistry & Technology Letters, 2021)
Purpose of the study: Heavy metals in food (vegetables, etc.) are harmful to humans due to their non-biodegradable nature, long biological half-lives, and their potential to accumulate in different body parts. Prolonged consumption of such heavy metal contaminated vegetables through foodstuffs may lead to chronic accumulation of heavy metals in human beings’ kidneys and liver, disrupting numerous biochemical processes, leading to cardiovascular, neural, kidney and bone diseases. Method: The study on heavy metal concentrations in vegetables grown in the command areas of Varthur lake, Bangalore. The collected vegetable samples were analyzed using ICP-OES (Inductively Coupled Plasma-Optical Emission Spectroscopy) technique to assess the level of heavy metal in acid digested samples. Main Findings: The study has shown a significant accumulation of heavy metals in vegetables that correlated well with its concentrations in soil and lake water. The prolonged irrigation of vegetables using contaminated lake water has led to soil contamination, which ultimately resulted in contamination of vegetables due to the uptake and accumulation of heavy metals in edible portions of vegetables. Application of the Study: Urgent attention is needed to devise and implement appropriate means of regular monitoring of the toxic heavy metals from domestic sewage and industrial effluent and provide proper advice and support for the safe and productive use of wastewater for irrigation purposes to prevent excessive buildup of heavy metals in the food chain.